Evaluation of magnetic susceptibility artefact induced by personal care product with gold nanoparticles on brain magnetic resonance (MRI) images - Zaini, Nor Syaza; Mohd, Zanariah; Abdul Karim, Muhammad Khalis (Institute of Physics Publishing, 2019)
MRI is an important diagnostic imaging tool as it provides excellent soft tissue contrast resolution. Artefact in MRI is an undesirable appearance in the image that affect the image quality and may hinder true diagnosis of the pathological events. Gold in bulk form does not cause any artefact in MRI as it is diamagnetic whereas in its nanoscale version, it was proven to pose magnetic properties. Previous studies also shown that some personal care products (PCPs) produce artefact in MR images due to the presence of metallic compounds in the PCP. Hence, this study was conducted to investigate the effect of PCP with gold nanoparticles (AuNPs) on brain MRI images. The study was conducted using 1.5 Tesla MRI system where moisturiser and compact powder with AuNPs were tested. The products were applied onto the micropore tape attached to the MRI water phantom. The phantom was placed in an RF coil at the isocentre of the MRI bore and scanned using T1-weighted fast-spin-echo (FSE), T2-weighted FSE and fluid attenuated inversion recovery (FLAIR) sequences. The images were evaluated using Visual Grading Analysis (VGA) checklist by two radiologists. Based on the VGA score, brain MRI images in moisturiser group were all scored ‘1’ which indicate minimal artefact with only loss of fine details seen. Whereas, brain MRI images of compact powder group were all scored ‘0’ which indicate no artefact seen. Therefore, it can be concluded that PCP with AuNPs produce little to no artefact on brain MRI images, thus, there will be no need for the patient who wears PCP with AuNPs to clean their face prior to brain MRI examination.